ANALISIS COLLABORATIVE GOVERNANCE DALAM PENGEMBANGAN DESA WISATA DI DESA RAHTAWU KECAMATAN GEBOG KABUPATEN KUDUS - Amelia Dwi Anggraini; Satria Aji Imawan (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
This study explain the implementation of collaborative governance in the development of Rahtawu Tourism Village using the collaborative dynamics framework of Emerson and Balogh and the collaboration success factors proposed by Mattessich and Monsey. The findings indicate that collaborative governance in Rahtawu Village has not been optimally implemented. In the collaborative dynamics aspect, shared principles, shared motivation, and joint capacity for action remain constrained by differences in actors’ perspectives and limited human resource capacity. Nevertheless, transparency and face-to-face dialogue facilitated through BUMDes, village deliberation forums, and village development planning meetings have gradually fostered shared goals oriented toward community welfare and village self-reliance. Collaborative actions are reflected in MSME assistance programs, tourism village socialization, comparative studies, and cultural events. The impacts of collaboration are evident in improved village economic performance, institutional strengthening, and the development of local-based business units. From Mattessich and Monsey’s perspective, environmental support, shared goals, communication, organizational structure, membership, and resources generally support collaboration, although human resource limitations remain a key challenge.